2011
DOI: 10.4103/0975-5950.85845
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and oral health

Abstract: Probiotics utilize the naturally occurring bacteria to confer health benefits. Traditionally, probiotics have been associated with gut health, and are being mainly utilized for prevention or treatment of gastrointestinal infections and disease; however, recently, several studies have suggested the use of probiotics for oral health purposes. The aim of this review is to understand the potential mechanism of action of probiotic bacteria in the oral cavity and summarize their observed effects with respect to oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Therefore, our study also suggested that OADC is the best supplement for biofilm growth as agreed by Nyvad and Fejerskov [24]. Mycobacterium smegmatis developed moderate biofilm at 30 C and strong biofilm at 42 and 37 C. Mycobacterium smegmatis demonstrates rapid growth on solid media over the temperature range of 24-45 C [7].…”
Section: Analysis Of M Tuberculosis H37rv Biofilm Formationmentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, our study also suggested that OADC is the best supplement for biofilm growth as agreed by Nyvad and Fejerskov [24]. Mycobacterium smegmatis developed moderate biofilm at 30 C and strong biofilm at 42 and 37 C. Mycobacterium smegmatis demonstrates rapid growth on solid media over the temperature range of 24-45 C [7].…”
Section: Analysis Of M Tuberculosis H37rv Biofilm Formationmentioning
confidence: 57%
“…Excess available carbon and the limitation of nitrogen, potassium or phosphate promote EPS and thickness of biofilm [6]. Colonies can vary widely in morphology, and there is a clear correlation between highly structured morphologies and the ability of a cell to produce an ECM [7]. Biofilms can form on almost any abiotic or biologic surface and it is estimated that 65% of all human bacterial infections involve biofilms.…”
mentioning
confidence: 99%
“…Also Lactobacillus fermentum appears to be promising. Hasslof P et al (2010) found that two L. plantarum strains and L. reuteri ATCC 55730 displayed the strongest inhibition on Candida albicans 16,21,26,47,52,53 . B. animalis reduces the incidence and severity of mucosal candidiasis 27 .…”
Section: Candidiasismentioning
confidence: 99%
“…(Narwal A et al, 2011, Tiwari G et al, 2012, Calafiore A et al, 2012, Rastogi P et al, 2011, Kumar A et al, 2013 Compete for nutrients and growth factors.…”
Section: Saccharomyces Boulardiimentioning
confidence: 99%